Self-regulation as a mediator in the relationship between self-efficacy, task value and active procrastination - Taura, Ali Abdullahi; Abdullah, Maria Chong; Roslan, Samsilah; Omar, Zoharah (Center for Promoting Ideas (CPI), 2014)
This study investigated the relationships between self-efficacy, task value, and active procrastination; and what role does self-regulation strategies play in these relationships. A total of 426 pre-service teachers, 223 males and 203 females, studying in colleges of education in North-Western Nigeria participated in the study. A set of self-report questionnaire was used to assess the participants’ levels of procrastination, self-efficacy, task value beliefs, and self-regulation strategies. Structural equation modelling (SEM) was employed as statistical technique for data analysis of the study. The results, based on the hypothesized structural model, which overall goodness-of-fit indices indicate good model fit, revealed that self-efficacy and task value beliefs were not directly significant predictors of active procrastination. However, mediation analysis, which was conducted based on SEM or modern approach, showed that there was an evidence of indirect effect of the variables on active procrastination through self-regulation. Test of mediation by bootstrapping method established significant mediating role of self-regulation in the relationship between self-efficacy, task value and active procrastination. Theoretical and practical implications of the study, as well as recommendations for future research, have been presented.